Time Effect of Disconfirmation pada Marketplace Shopee di Yogyakarta - Irma Nursafitri; Ida Bagus Nyoman Udayana (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Indonesian society is a heterogeneous society because it consists of many tribes, cultures and layers of society. Therefore, their shopping tastes also vary. For this reason, Indonesia has many offline and online stores. But now people prefer to shop at online stores, because shopping at online stores is easier, more convenient, and saves more time and energy. Shopee is one of the marketplaces in Indonesia. Shopee is the number one online shopping in Indonesia this year. Its activities have penetrated all markets in Indonesia. Customer expectations for a product exist because they cannot see the product they are going to buy directly. Customer expectations greatly affect customer satisfaction. Because they are mutually exclusive. Positive disconfirmation is influenced by customer expectations. If expectations are met then repurchase intention will occur. Research shows that customer expectations on the Shopee marketplace are valid and significant to customer satisfaction. Positive disconfirmation is also valid and significant to customer satisfaction. Customer satisfaction has a positive effect on the intention to repurchase. Therefore, the Shopee marketplace must maintain credibility so that customers always trust and continue to use the Shopee marketplace as a platform for online shopping. Shopee also has to maintain brand awareness so that it is always remembered and used as a leading marketplace in Indonesia. Keywords: online shopping, expectation theory, disconfirmation, satisfaction, repurchase intention.